Two Transitions: A Brief on Analyses and Policies for MENA and CESEE - Vladimir Gligorov (The Vienna Institute for International Economic Studies (wiiw), 2012)
One year after the onset of the Arab Spring, the transition is clearly at its very beginning. In that, it does not compare with the onset of transition in Central, East and Southeast Europe (CESEE) in 1989 or 1990, which was a kind of breakthrough and provided a clear discontinuity with the past in almost all respects. In the majority of cases this has been one more step in the process of systemic change in the CESEE that will take some time to unfold. This Policy Note compares changes in the Middle East and North Africa (MENA) with the processes of reforms and change that took place in the socialist world from, arguably, 1956 to 1989. It is hard to time the current turmoil in the MENA region in comparison with the long process of reforms and transition in CESEE, but it could be argued that in most cases the 1989 moment is yet to come to the former region. ...
Keywords: 330